THE IMPACT OF BROKEN HOME FAMILIES ON THE MORAL AND PSYCHIC DEVELOPMENT OF GRADE VI ELEMENTARY SCHOOL STUDENTS - Wulandari, Nyimas; wantini, Wantini; Diponegoro, Ahmad Muhammad (Psikoislamedia: Jurnal Psikologi, 2024)
The results of the teacher's daily research show that children from broken home families often make noise during class hours, this is because the child seeks attention to others. This then prompted the author to conduct a study that focused on broken home children with the aim of conducting a case study which then examined more deeply the impact of broken home families on the moral and psychic development of grade VI elementary school students at SD N 1 Sribitan. By using quality research with a case study approach. Participants in this study the author chose based on backgrounds and behaviors that stood out while in school using purposive samples so that two students were found who stood out from five students who had the same background, namely class VI SDN 1 Sribitan, namely A.C.P and .P.D.A. The results obtained from this study are an illustration that the influence or impact of broken home families is very real in terms of children's moral and psychic development. In this study, it can be explained that the bad moral problems that participants often do are not wanting to apologize if they are wrong, making noise, and not obeying the rules that have been applied in schools.